Case Report: A Relatively Mild Phenotype Produced by Novel Mutations in the SEPSECS Gene - Rong, Tingyu; Yao, Ruen; Deng, Yujiao; Lin, Qingmin; Wang, Guanghai; Wang, Jian; Jiang, Fan; Jiang, Yanrui (Frontiers in Pediatrics, 2022)
Mutations in the human O-phosphoseryl-tRNA:selenocysteinyl-tRNA synthase gene (SEPSECS) are associated with progressive cerebello-cerebral atrophy (PCCA), also known as pontocerebellar hypoplasia type 2D (PCH2D). Early-onset profound developmental delay, progressive microcephaly, and hypotonia that develops toward severe spasticity have been previously reported with SEPSECS mutations. Herein we report a case with severe global developmental delay, myogenic changes in the lower limbs, and insomnia, but without progressive microcephaly and brain atrophy during infancy and toddlerhood in a child harboring the SEPSECS missense variant c.194A>G (p. Asn65Ser) and a novel splicing mutation c.701+1G>A. With these findings we communicate the first Chinese SEPSECS mutant case, and our report indicates that SEPSECS mutations can give rise to a milder phenotype.